2015
DOI: 10.1088/0967-3334/36/3/441
|View full text |Cite
|
Sign up to set email alerts
|

Time-frequency analysis of heart rate variability during the cold pressor test using a time-varying autoregressive model

Abstract: Heart rate variability is a useful clinical tool for autonomic function assessment and cardiovascular disease diagnosis. To investigate the dynamic changes of sympathetic and parasympathetic activities during the cold pressor test, we used a time-varying autoregressive model for the time-frequency analysis of heart rate variability in 101 healthy subjects. We found that there were two sympathetic peaks (or two parasympathetic valleys) when the abrupt changes of temperature (ACT) occurred at the beginning and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…We first evaluated the proposed methodology during a paradigmatic ANS elicitation through prolonged cold-pressor test (CPT) in twenty six healthy volunteers. The significant decrease in μ RR following the CPT onset is consistent with previous studies (see 29 and references therein), and RMSSD and pNN50 also showed a significant decrease in specific time windows. Note that significant p-values were obtained from standard EDA measurements (F 4 ) at all time intervals from the CPT onset, and a delayed response in EDA Symp of about 30s from the CPT onset was also observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We first evaluated the proposed methodology during a paradigmatic ANS elicitation through prolonged cold-pressor test (CPT) in twenty six healthy volunteers. The significant decrease in μ RR following the CPT onset is consistent with previous studies (see 29 and references therein), and RMSSD and pNN50 also showed a significant decrease in specific time windows. Note that significant p-values were obtained from standard EDA measurements (F 4 ) at all time intervals from the CPT onset, and a delayed response in EDA Symp of about 30s from the CPT onset was also observed.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the significant effect of CPT on left ventricular function has been demonstrated in a recent study 28 . These studies have shown major changes in heart rate and blood pressure during the CPT phase in healthy subjects 29 , as well as in patients with pathological conditions such as hypertension 30 , depression 31 , and anxiety 32 . Nevertheless, due to methodological limitations results were controversial [29][30][31][32] .…”
mentioning
confidence: 99%
“…In fact, non-baroreflex-mediated sympathetic neural control in humans has been evaluated using CPT in both clinical and experimental settings [8]- [10]. Exemplarily, heart rate and blood pressure responses to the CPT were assessed in male and female healthy subjects [11], [12], as well as hypertension [13] and depression [14].…”
Section: Introductionmentioning
confidence: 99%
“…When exercising in hot environments, heat tolerance indexed with CVA can be improved through frequent exposure, but the effects disappear after frequent heat exposure stops (Flouris et al, 2014). Finally, abrupt changes in temperature lead to a CVA withdrawal, before the organism adapts (Peng et al, 2015). To sum up, CVA appears to be increased by cold environments, whereas hot environments tend to decrease CVA.…”
Section: Temperaturementioning
confidence: 99%